On strictly cosingular operators - Vladimirski, J. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Ю. Н. Владимирский. О строго косингулярных операторах J. Vladimirskis. Apie griežtai kosinguliarinius operatorius